Features and Fillers : Texas Journalists on Texas Folklore - Satterwhite, Carolyn Fiedler; Harris, Jim, 1942- (Book collections on Project MUSE., 1999)
Discusses El ojo, Rattlesnake roundups, and chicken-fried steak, and other important novelties of Texas.